Taboo in Balinese Language Spoken in Puri Tukadmungga - Agita, Anak Agung Ayu Ngurah (STKIP Agama Hindu Singaraja, 2023)
This study explores the use of taboo language in the Balinese language spoken in Puri Tukadmungga, focusing on the identification and categorization of taboo words across different domains. The study successfully identifies 23 taboo words within the